Analysis of the Influence of the School Environment on Student Satisfaction at the Nur Ihsan School in Medan - Rizka Hidayah Husin Lubis (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of the school environment on student satisfaction at the Nur Ihsan School, Medan. This research is motivated by the importance of understanding how the school environment contributes to student well-being and overall satisfaction. This research uses a quantitative approach by utilizing survey instruments to collect data from a sample of students at Nur Ihsan School. Data analysis includes descriptive statistics and regression analysis to examine the relationship between various elements of the school environment and student satisfaction. Research findings reveal significant correlations between certain aspects of the school environment, such as physical facilities, quality of teaching, peer relationships, and student satisfaction. This research emphasizes the importance of a positive school environment in helping to increase student satisfaction and engagement. The implications of these findings suggest that educational institutions should prioritize improving the physical and social aspects of the school environment to increase student satisfaction. This research contributes to the broader conversation about educational quality and student well-being, by providing insight into the factors that contribute to a better educational experience positive